Relationship between Fibre Characteristics and Physico-Mechanical Properties of Aningeria robusta (A.CHEV) Wood - K.O., Olaoye; A.O., Oluwadare; O.S., Ariwoola (International Journal of Environment, Agriculture and Biotechnology, 2019)
Aningeria robusta wood is fast becoming popular in Nigeria, due to its excellent performance in structural applications especially in roofing, and in recent times, door frames and furniture. Thus, consideration must be given to its mechanical properties, and fibres in wood is known for providing mechanical support for the wood. Notwithstanding, mechanical failure of wood in service still occurs. To limit such failures assessment is needed to be done on some parameters associated to quality of wood. This study thus assess the relationship between fibre characteristics and physico-mechanical properties of Aningeria robusta wood. Three trees of Aningeria robusta were obtained wood samples of 20x20x300mm were collected to determine modulus of elasticity and modulus of rupture (mechanical property), 20X20X20mm for fibre characteristics, and 20x20x60mm for wood density and moisture content. The mean fibre length, fibre diameter, lumen, cell wall thickness (CWT), 1.55mm, 11.71μm, 8.78μm, 1.46μm, while the mean moisture content, density, modulus of rupture (MOR) and modulus of elasticity (MOE) were 55.54%, 429.34kg/m3, 123.91N/mm2, 5876.89N/mm2 respectively. There existed a negatively significant correlation between fibre length and MOR, and well as CWT and moisture content. This existing relationship implies that the shorter the fibre length, the more the MOR. It can therefore be concluded that existing relationship between fibre characteristics and physico-mechanical properties taken cognisance of where mechanical failure of wood is to be limited.